The Creature - Chakravarty, Prasanta (Bloomsbury Publishing India Pvt. Ltd., 2021)
Intro – Half Title – Title Page – Copyright – Contents – Introduction: The Omen of Nothing – Book I – I. The Imitative Creature – II. The Hounded Creature – III. The Creature Forlorn – IV. The Elsewhere Creature – V. The Creature in Action – Book II – VI. The Observant Creature – VII. The Generous Creature – VIII. The Creature as the Spirit-Wrestler – Book III – IX. The Plastic Creature – X. The Creature as the Blasted Mortar – XI. The Creature Aflutter – XII. The Enchanted Creature – XIII. The Upright Creature – Book IV – XIV. Decreature – Index – About the Author.
Description based on publisher supplied metadata and other sources
Keywords: Suffering in literature; Mimicry (Biology); Agonistic behavior in animals; Electronic books